The Influence of Occupational Stress on Turnover Intention with Perceived Labor Market Condition as a Mediating Variable at PT IMB Yogyakarta - Maharani Maharani; Syamsul Hadi; Kusuma Chandra Kirana (INTERNATIONAL JOURNAL OF ECONOMICS AND MANAGEMENT REVIEW, 2025)
Purpose - This study aims to examine the influence of occupational stress on employees' turnover intention at PT IMB Yogyakarta, with perceived labor market condition as a mediating variable. Design/methodology/approach - The approach used in this study is quantitative with a survey method. The research sample consisted of 94 employees at PT IMB Yogyakarta selected using a non probability sampling.technique. Data analysis was conducted using Partial Least Squares Structural Equation Modeling (PLS-SEM) with the SmartPLS software. Originality -  This study contributes to the understanding of how occupational stress impacts employees' intention to leave an organization, and how perceived labor market condition plays a role in mediating that relationship, especially within the high-pressure work culture context of a private company. Findings and Discussion - The findings indicate that occupational stress has a positive and significant effect on turnover intention. However, perceived labor market condition also plays an important role by mediating the impact of stress. Employees who perceive that external job opportunities are limited may delay their resignation decisions even under stressful conditions. Conclusion - These results suggest that reducing occupational stress and improving job satisfaction are essential to retaining employees. Additionally, understanding the dynamics of perceived labor market conditions can help companies develop better HR strategies in competitive environments.